Neurogenesis and Viral Infection - Ihunwo, Amadi Ogonda; Perego, Jessica; Martino, Gianvito; Vicenzi, Elisa; Panina-Bordignon, Paola (Frontiers in Immunology, 2022)
Neural stem cells (NSCs) are multipotent stem cells that reside in the fetal and adult mammalian brain, which can self-renew and differentiate into neurons and supporting cells. Intrinsic and extrinsic cues, from cells in the local niche and from distant sites, stringently orchestrates the self-renewal and differentiation competence of NSCs. Ample evidence supports the important role of NSCs in neuroplasticity, aging, disease, and repair of the nervous system. Indeed, activation of NSCs or their transplantation into injured areas of the central nervous system can lead to regeneration in animal models. Viral invasion of NSCs can negatively affect neurogenesis and synaptogenesis, with consequent cell death, impairment of cell cycle progression, early differentiation, which cause neural progenitors depletion in the cortical layer of the brain. Herein, we will review the current understanding of Zika virus (ZIKV) infection of the fetal brain and the NSCs, which are the preferential population targeted by ZIKV. Furthermore, the potential neurotropic properties of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which may cause direct neurological damage, will be discussed.